1999
DOI: 10.1577/1548-8675(1999)019<0724:reiaor>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Regional Economic Impact Assessments of Recreational Fisheries: An Application of the IMPLAN Modeling System to Marine Party and Charter Boat Fishing in Maine

Abstract: Regional economic impact assessments (EIAs) of recreational fisheries reveal how anglers' expenditures affect economic activity such as sales, income, and employment in a particular region. Unfortunately, most EIA studies report only the final impacts of the EIA, without describing the economic interdependencies that produced the impacts or how the results should and should not be used to guide management decisions. This is particularly troublesome because most resource managers only vaguely understand how EIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…The economic impact of MRF has been estimated as being both positive and valuable in many regions (STEINBACK, 1999;FRANQUESA et al, 2004;COWX & ARLINGAUS, 2008) but in this case the impact was the opposite. The results showed, with the exception of the underwater fishing type, that the catch value of MRF was considerably higher than the associated fishing costs of this activity.…”
Section: Discussionmentioning
confidence: 99%
“…The economic impact of MRF has been estimated as being both positive and valuable in many regions (STEINBACK, 1999;FRANQUESA et al, 2004;COWX & ARLINGAUS, 2008) but in this case the impact was the opposite. The results showed, with the exception of the underwater fishing type, that the catch value of MRF was considerably higher than the associated fishing costs of this activity.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include assessments of the impacts of changes in National Forest harvest policies (Summers and Birss 1991), federal grazing policies (Geier and Holland 1991), community development strategies (Geier et al 1994), and regulatory changes in management of commercial crab fisheries o¤ Alaska (Natcher 1996) and guided sport fisheries o¤ New England (Steinback 1999). We selected IMPLAN (Olson and Lindall 1997) as a base for our model.…”
Section: Input-output Modelmentioning
confidence: 99%
“…International studies have focused mainly on different aspects of recreational fishing rather than on fishing tourism and its economic impacts as such. Examples of this are the economic impacts of recreational rod anglers in Scotland (Butler et al, 2009), the extent of recreational fishing as tourism at the state level in the United States (Ditton et al, 2002), the economic benefits of sport fishing in Pennsylvania, USA (Upneja et al, 2001), and the regional economic impact assessments of recreational fisheries in Maine, USA (Steinback, 1999). Some recent studies on salmon angling tourism can be found, but they have not focused on the economic impacts of fishing tourism (Stensland, 2010(Stensland, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The input-output method is widely applied in assessing the economic impacts of recreational fishing (see Steinback, 1999;Upneja et al, 2001;Butler et al, 2009;Parkkila et al, 2010). Generally speaking, the input-output method is used in tourism research when studying the economic impacts of tourism at the national (e.g.…”
Section: Introductionmentioning
confidence: 99%